Implementation of Cellular IoT over VANETs for Efficient Communication of Safety Messages (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
when it comes to communication of road safety message communication, improved packetdelivery ratio, reduced delay in packet delivery are most important as the messages are critical andneed to be communicated and guaranteed delivery. Along with the better delivery parameters weenergy efficiency is also an important factor. This paper introduces a method to implement VANETsusing LTE-M against WAVE which is particularly concentrating on different types of communicationsin VANETs. With the adaption of LTE-M in the VANETs the model gives some designsimplifications. This raise to reduction of unnecessary stages in cluster formation such as Cluster Headsin vehicles and allow communication of vehicles directly via RSU which will reduce the no of hopsbetween sender and receiver when the cluster head is more than 2 hops from sender to receiver. Thiswill also reduce the computation burden on cluster head. So we achieve better delivery ratio andreduced delay in delivering packets.